Missed Opportunities for Early De-Escalation of Antipseudomonal Beta-Lactam Antimicrobial Therapy in Enterobacterales Bloodstream Infection - Mollie Reese; P. Brandon Bookstaver; Joseph Kohn; Casey Troficanto; Emily Yongue; Hana R. Winders; Majdi N. Al-Hasan (Antibiotics)
Background: Antipseudomonal β-lactams (APBL) are commonly used for empirical therapy of Gram-negative bloodstream infections (BSI). This retrospective cohort study examines risk factors for prolonged APBL use (≥48 h) in patients with Enterobacterales BSI and compares 28-day mortality between early de-escalation of APBL and prolonged APBL therapy. Methods: Adult patients admitted to two community hospitals in South Carolina with Enterobacterales BSI from January 2010 to June 2015 were included in this study. Data were extracted manually from medical records. Multivariate logistic regression and Cox proportional hazards analyses were used to examine predictors of prolonged APBL therapy and mortality, respectively. Results: Among 993 patients with Enterobacterales BSI, 491 (49%) underwent early de-escalation of APBL and 502 (51%) received prolonged APBL therapy. Cancer, immune compromised status, residence at a skilled nursing facility, a high Pitt bacteremia score, non-urinary source of infection, and BSI due to AmpC-producing Enterobacterales were independently associated with prolonged use of APBL. Antimicrobial stewardship interventions were inversely associated with prolonged APBL use. Early de-escalation of APBL was not associated with increased mortality. Conclusions: This study exemplifies the safety and effectiveness of early de-escalation of APBL in Enterobacterales BSI. Antimicrobial stewardship strategies should be implemented to encourage the practice of early de-escalation of antimicrobial therapy, including in high-risk populations.